Effects of sodium-glucose cotransport-2 inhibitors treatment in patients with pulmonary hypertension - Mohammed Obeidat; Aravinthan Vignarajah; Rashid Abdel-Razeq; Ala’eddien Nathir; Nishanthi A. Vigneswaramoorthy; Adriano R. Tonelli (Therapeutic Advances in Respiratory Disease, 2025)
Background: Pulmonary hypertension (PH) is a complex disorder associated with various underlying conditions, including cardiac and respiratory diseases. PH is classified into five groups based on etiology, disease mechanisms, hemodynamic data, and treatment options. Preliminary data suggest that sodium-glucose cotransport-2 inhibitors (SGLT2-I), known for their benefits in chronic kidney disease, heart failure, and type-2 diabetes mellitus, may have therapeutic implications in PH through their metabolic effects, which include reducing aerobic glycolysis, improving mitochondrial function, and enhancing fatty acid oxidation. Objective: This study aimed to evaluate the clinical effects of SGLT2-I in PH by analyzing a large multicenter database of medical records from the TriNetX Network. Design: The cohort included adult patients with PH diagnosed between January 1, 2012, and January 1, 2023, classified by PH group and treatment with SGLT2-I. Propensity score matching (PSM) was used to balance baseline characteristics between the SGLT2-I and non-SGLT2-I groups. Methods: The primary endpoint was a composite of all-cause mortality, RHF, and hospital admissions over 365 days. Secondary endpoints included the individual components of the primary endpoint, intubations, RHF incidence, IV diuretic use, and NT-Pro-BNP levels. PSM was used to adjust for baseline differences between cohorts. Results: A total of 771,490 patients with PH were identified, with 58,303 treated with SGLT2-I. After PSM, each cohort of treated and untreated patients included 58,302 patients. Patients treated with SGLT inhibitors had a significant reduction in the primary composite endpoint (HR 0.71, 95% CI: 0.707–0.729). Secondary outcomes, including all-cause mortality, hospitalization, and the number of intubations, were also significantly lower in patients treated with SGLT-2 inhibitors. Beneficial effects of SGLT2-I were observed across all PH groups. Conclusion: This study demonstrates that SGLT2-I may be clinically beneficial in patients with PH by reducing all-cause mortality, RHF, and hospital admissions. Our findings support the role of SGLT2-I as a therapeutic option in PH and provide support for future randomized controlled trials using this treatment.